Pengaruh Kecukupan Modal (CAR), Pengelolaan Kredit (NPL), dan Likuiditas Bank (LDR) Terhadap Probabilitas Kebangkrutan Bank (Studi pada Bank Umum Swasta Devisa yang tercatat di BEI tahun 2009 – 2013) - Hidayati, Lina Nur (JURNAL ILMU MANAJEMEN, 2015)
The purpose of this research is to provide empirical evidence about using bank financial ratio to predict bank bankruptcy. The variables which used are seven financial ratios, CAR (capital adequacy ratio), NPL (non performing loan), and LDR (loan to deposit ratio). The statistic methods which is used to test on the research hypothesis is logit regression.The sample of this research was extracted using purposive sampling method, comprising 7 banks taken from BEI for the period of 2009, 2010, 2011, 2012, 2013. From sample, there are 7 banks, consist of 4 nontrouble banks and 3 trouble banks. The resulst of this research show that CAR and NPL, have no significant effect on probability of banks's financial distress. LDR have significant influences on probability of banks's financial distress.Keywords :